Tinjauan Pustaka Sistematis Alat Permainan Edukatif: Kriteria Alat Permaianan Edukatif AUD untuk Literasi Pendidikan Lingkungan Lahan Basah - Doddyansyah, Muhammad Rusvendy; Novitawati, Novitawati; Fitria, Fadilatul (Early Stage, 2025)
The purpose of writing this article is to recognize the criteria for APE that can increase AUD literacy about environmental education, especially wetlands. This article uses the literature review method with a mapping review approach. Literature review is carried out by searching for relevant articles, determining extraction criteria, analyzing, and synthesizing at the final stage. The data sources used to find references are Google Scholar. The results of the literature rivew show that Educational Game Tools for early childhood with wetland content prioritize hands-on, heads-on, and hearts-on experiences. Some forms of media are: 1) Conventional board games; 2) Digital board games; and 3) Folk games. The content of this media can also be developed on the suitability of wetland conditions around the school such as: 1) Swamp animals; 2) Activities in the swamp; and 3) Healthy swamp environment